2021
DOI: 10.1002/adhm.202002275
|View full text |Cite
|
Sign up to set email alerts
|

A Biomimetic In Vitro Model of the Kidney Filtration Barrier Using Tissue‐Derived Glomerular Basement Membrane

Abstract: The glomerular filtration barrier (GFB) filters the blood to remove toxins while retaining high molecular weight proteins in the circulation. The glomerular basement membrane (GBM) and podocytes, highly specialized epithelial cells, are critical components of the filtration barrier. The GBM serves as a physical barrier to passage of molecules into the filtrate. Podocytes adhere to the filtrate side of the GBM and further restrict passage of high molecular weight molecules into the filtrate. Here, a 3D cell cul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 81 publications
0
4
0
Order By: Relevance
“…Additionally, within the native glomerulus, the fenestrated capillary endothelial barrier restricts the passage of molecules smaller than 70 kDa 66 ; the basement membrane, with its negative charge, also limits the passage of particles movement and favors the filtration of cations. Foot processes on podocytes provide an additional size selectivity as they wrap around the glomerular capillary loop to form interdigitated filtration slits with a spacing of approximately 40 nm 67 . By removing this intrinsic selectively permeable barrier through decellularization, macromolecular transport was no longer limited by size, shape, charge, and deformability 68 .…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, within the native glomerulus, the fenestrated capillary endothelial barrier restricts the passage of molecules smaller than 70 kDa 66 ; the basement membrane, with its negative charge, also limits the passage of particles movement and favors the filtration of cations. Foot processes on podocytes provide an additional size selectivity as they wrap around the glomerular capillary loop to form interdigitated filtration slits with a spacing of approximately 40 nm 67 . By removing this intrinsic selectively permeable barrier through decellularization, macromolecular transport was no longer limited by size, shape, charge, and deformability 68 .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, within the native glomerulus, the fenestrated capillary endothelial barrier restricts the passage of molecules smaller than 70 kDa (Hamano et al, 2002); the basement membrane, with its negative charge, also limits the passage of particles movement and favors the filtration of cations. Foot processes on podocytes provide an additional size selectivity as they wrap around the glomerular capillary loop to form interdigitated filtration slits with a spacing of approximately 40 nm (Wang et al, 2021). By removing this intrinsic selectively permeable barrier through decellularization, macromolecular transport was no longer limited by size, shape, charge, and deformability (Venturoli and Rippe, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…In this context, in vitro models of the GFB have been developed using a variety of methods (e.g. microfluidic, microfabrication, organoids, and tissue-derived glomerular basement membrane) to better recapitulate the in vivo microenvironment [9][10][11][12][13][14][15][16][17]. For example, Musah et al demonstrated a polydimethylsiloxane (PDMS)-based microfluidic platform that encompassed two microfluidic channels parted by an extracellular-matrix-coated-PDMS porous membrane, in which the GEs and podocytes were, respectively, seeded on the top and bottom sides of the porous membrane [10].…”
Section: Introductionmentioning
confidence: 99%